Implikatur Tegur Sapa Dalam Bahasa Rejang Di Kecamatan Tubei Kabupaten Lebong - Putri, Dwi Adesi; Zakaria, Jelita; Mahdijaya, Mahdijaya; Gunawan, Hafiz (Jurnal Multidisiplin Dehasen (MUDE), 2025)
This study aims to describe the implicature of greeting in Rejang language in tubei District of lebong Regency. This study examines the implicature in Rejang language greeting in Tubei Sub-District as a form of communication that reflects cultural values, such as politeness and familiarity, through implied meanings in everyday speech. The problem in this study is how the implicature in Rejang language in tubei District of lebong Regency. The method used is descriptive qualitative. The Data in this study is the implicature of greeting in Rejang language in Tubei District of Lebong Regency, the source of the data is the Rejang language user community in Tik teleu village. The technique of data collection is done by free fold cakap listening technique, Record Technique and recording technique. Data analysis is done by grouping the data, followed by analyzing the data to become a foundation in the process of interpretation, interpretation of all data and conclude the results of the study. The results of this study are conversation implicature and conventional implicature. The more dominant implicature appearing in this study is the conventional implicature. For the future, the author hopes that students of the Faculty of Teacher Training and Indonesian language and literature education will gain insight into the implications of greeting.